PENAFSIRAN KISAH PARA RASUL1:8 DAN IMPLEMENTASI MISI PEMBERITAAN INJIL LINTAS BUDAYA - Bartholomeus Diaz Nainggolan (Jurnal Koinonia, 2013)
The problem in this research is there is awareness that evangelism missions are the churches essential.Â  But in the implementation of this missions are depended on how the churches interpret the Bible fundamental verses about those missions. The church interpretation itself is depended on the interpretation of their pastors. The Bible interpretation which is understood by the Pastor is touched to the congregation and then it will be generally implemented in congregation’s daily life or in the church programs.